2017
DOI: 10.1177/1934578x1701200618
|View full text |Cite
|
Sign up to set email alerts
|

New Steroidal Glycoside and Flavonoid Constituents from Ophiopogon japonicus

Abstract: Chromatographic separations of a methanolic extract of Ophiopogon japonicus tubers resulted in the isolation of a new steroidal glycoside, (25R)-ruscogenin 1-O-(4-O-sulfo)-β-D-fucopyranoside (1), a new C-methylflavonol, 3,4′-dimethoxy-3′,5,5′,7-tetrahydroxy-8-methylflavone (2), and a known flavonol, 3,4′dimethoxy-3′,5,5′,7-tetrahydroxyflavone (3). The C-methylflavonol was reported for the first time from the genus Ophiopogon. Compound 1 showed moderate cytotoxicity against SK-Mel-2 and KB cells with IC 50 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that steroidal saponins and homoisoflavones are the major components of this formulation, including ophiopogonin D, ophiopogonin D , dioscin, methylprotodioscin, officinalisnin-II, aspacochinosides N, aspacochinosides O, aspacochinosides P, ophiopogonanone D and Methylophiopogonone B, etc. [2][3][4][5][6][7][8][9][10][11], which displays significant anti-inflammatory, antibacterial, antioxidant and immunomodulatory activities [12][13][14][15][16][17][18]. EDG modulates inflammatory responses and has been employed to prevent and treat pulmonary diseases; such as acute lung injury (ALI) by reducing pulmonary edema, and the secretion of TNF-α and IL-6, and increasing the expression of aquaporin-1 (AQP-1) and aquaporin-5 (AQP-5) proteins in the lung tissue [19]; it also markedly reduces the expression of TNF-α, interleukin-10 (IL-10), and transforming growth factor-β1 (TGF-β1) and promotes the apoptosis of gastric cancer cells to delay the occurrence and development of lung tumors in Molecules 2023, 28, 295 2 of 16 rats [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that steroidal saponins and homoisoflavones are the major components of this formulation, including ophiopogonin D, ophiopogonin D , dioscin, methylprotodioscin, officinalisnin-II, aspacochinosides N, aspacochinosides O, aspacochinosides P, ophiopogonanone D and Methylophiopogonone B, etc. [2][3][4][5][6][7][8][9][10][11], which displays significant anti-inflammatory, antibacterial, antioxidant and immunomodulatory activities [12][13][14][15][16][17][18]. EDG modulates inflammatory responses and has been employed to prevent and treat pulmonary diseases; such as acute lung injury (ALI) by reducing pulmonary edema, and the secretion of TNF-α and IL-6, and increasing the expression of aquaporin-1 (AQP-1) and aquaporin-5 (AQP-5) proteins in the lung tissue [19]; it also markedly reduces the expression of TNF-α, interleukin-10 (IL-10), and transforming growth factor-β1 (TGF-β1) and promotes the apoptosis of gastric cancer cells to delay the occurrence and development of lung tumors in Molecules 2023, 28, 295 2 of 16 rats [20].…”
Section: Introductionmentioning
confidence: 99%